Pengaruh Kualitas Pelayanan, Inovasi Produk dan Store Atmosphere terhadap Kepuasan Konsumen pada Warung Makan Sahabat Sego Sambel Warastratama Surakarta - Brigita Excel Vayla; Adcharina Pratiwi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study was conducted on consumers of Warung Makan Sahabat Sego Sambel Warastratama Surakarta. The purpose of this study was to analyze the significance of the influence of service quality, product innovation, store atmosphere on consumer satisfaction at Warung Makan Sahabat Sego Sambel Warastratama Surakarta. The type of data used is quantitative data. The data sources used in this study are primary and secondary data. The data analysis techniques used in this study are multiple linear regression analysis, classical assumption test, t test, F test, and coefficient of determination (????2). The results of the multiple linear regression analysis of this study are Y = 3.239 + 0.251 X1 + 0.212 X2 + 0.416 X3 + e. The results of the t test show a significant effect on consumer satisfaction at Warung Makan Sahabat Sego Sambel Warastratama Surakarta. The results of the F test show the right model in predicting the effect of service quality, product innovation, and store atmosphere on consumer satisfaction at Warung Makan Sahabat Sego Sambel Warastratama Surakarta. The results obtained from the Determination coefficient (????2) are 0.681, meaning that the contribution of the independent influence of X1 (service quality), X2 (product innovation) and X3 (store atmosphere) to Y (consumer satisfaction) is 68.1%. The rest (100% - 68.1%) = 31.9% is explained by other variables not included in this study..